Growth and maturation of pequi fruit of the Brazilian cerrado - Rodrigues,Luiz José (2015)
The objective of this study was to characterize the development of pequi fruit (Caryocar brasiliense) of the Brazilian cerrado. It takes 84 days (12 weeks) for pequi to develop with the onset of flowering in September and early fruit set in January. Pequi fruit showed a simple sigmoid growth curve, and its growth was characterized based on fresh mass and longitudinal and transverse diameters. The contents of titratable acidity, soluble solids, β-carotene, and vitamin C increased during fruit growth, reaching their maximum values at the 12th week (84 days) after anthesis. Pequi is a fruit with an extremely high respiratory activity; its respiratory rate decreased during its development. Pequi fruit has been classified as a non-climacteric fruit due to the decrease of both respiration and ethylene production rates during maturation and ripening.